Proposed new interior design scheme of ‘Scientific Excellence in Islamic Civilisation’ at Pusat Sains Negara, Persiaran Bukit Kiara, Bukit Kiara, 50662 Kuala Lumpur / Mohammad Zafran Abdul Rahim - Abdul Rahim, Mohammad Zafran (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to propose a new interior design scheme for the interior of ‘Scientific Excellence in Islamic Civilisation’ Interactive Gallery which is situated at Level 2, Pusat Sains Negara, Persiaran Bukit Kiara, Bukit Kiara, 50662 Kuala Lumpur. This proposed interactive gallery is to attract children, even adults to explore the history of pioneers of the greatest science by the great thinkers of Islam. The target market is not only in domestic, but also international visitors and it would be a huge advantage as Pusat Sains Negara is one of the most famous museum attractions in Malaysia. Because of the subject somes in different field of science, different galleries are created to differenciate each area. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the impact to every visitors and comfortable working environment for the workers in ‘Scientific Excellence in Islamic Civilisation’ Interactive Gallery. Connected to that, the chosen design style for ‘Scientific Excellence in Islamic Civilisation’ Interactive Gallery is based on Modern Islamic design, goes all the way with the client’s needs as it blends in with the subject matter which is the glorious years of Islam. Before getting a desired design that is suitable with the client’s needs, some data analysis should be done where these analysis is on types of customers to attend the session, types of services offered, products of the brand, spaces to be concluded in the proposed area, operation time and informations about other spas that use the same system in management, as the proposed spa. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.